The Effects of Saline Water Drip Irrigation on Tomato Yield, Quality, and Blossom-End Rot Incidence --- A 3a Case Study in the South of China. - Yaming Zhai; Qian Yang; Maomao Hou (PLoS ONE, 2015)
Saline water resources are abundant in the coastal areas of south China. Most of these resources still have not been effectively utilized. A 3-year study on the effects of saline water irrigation on tomato yield, quality and blossom-end rot (BER) was conducted at different lower limits of soil matric potential (-10 kPa, -20 kPa, -30 kPa, -40 kPa and -50 kPa). Saline water differing in electrical conductivity (EC) (3 dS/m, 4 dS/m, 4.5 dS/m, 5 dS/m and 5.5 dS/m) was supplied to the plant after the seedling establishment. In all three years, irrigation water with 5.5 dS/m salinity reduced the maximum leaf area index (LAIm) and chlorophyll content the most significantly when compared with other salinity treatments. However, compared with the control treatment (CK), a slight increase in LAIm and chlorophyll content was observed with 3~4 dS/m salinity. Saline water improved tomato quality, including fruit density, soluble solid, total acid, vitamin C and the sugar-acid ratio. There was a positive relationship between the overall tomato quality and salinity of irrigation water, as analyzed by principal component analysis (PCA). The tomato yield decreased with increased salinity. The 5.5 dS/m treatment reduced the tomato yield (Yt) by 22.4~31.1%, 12.6~28.0% and 11.7~27.3%, respectively in 2012, 2013 and 2014, compared with CK. Moreover, a significant (P≤0.01) coupling effect of salinity and soil matric potential on Yt was detected. Saline water caused Yt to increase more markedly when the lower limit of soil matric potential was controlled at a relatively lower level. The critical salinity level that produced significant increases in the BERi was 3 dS/m~4 dS/m. Following the increase in BERi under saline water irrigation, marketable tomato yield (Ym) decreased by 8.9%~33.8% in 2012, 5.1%~30.4% in 2013 and 10.1%~32.3% in 2014 compared with CK. In terms of maintaining the Yt and Ym, the salinity of irrigation water should be controlled under 4 dS/m, and the lower limit of soil matric potential should be greater than -20 kPa.